2006
DOI: 10.1203/01.pdr.0000246098.65888.5b
|View full text |Cite
|
Sign up to set email alerts
|

MxA-Based Recognition of Viral Illness in Febrile Children by a Whole Blood Assay

Abstract: Febrile children are often given antibiotics empirically and unnecessarily. MxA is a protein induced in peripheral lymphoid cells by type 1 interferons during active viral infection. The ability of a whole blood ELISA assay for MxA to identify children with viral illness was studied in 122 children who presented with acute onset fever and 52 age-matched healthy controls. The febrile children were divided into three groups according to their final diagnoses: etiologically diagnosed viral infection, clinically d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 42 publications
2
34
0
Order By: Relevance
“…Small-scale clinical studies have found promising results showing that MxA levels enable the differentiation of viral and bacterial infections. [5][6][7][8][9] The present prospective multicenter study was undertaken to confirm these findings in routine practice conditions in a larger patient population including different clinical syndromes and infections with different bacterial and viral pathogens. …”
Section: What This Study Addsmentioning
confidence: 66%
See 1 more Smart Citation
“…Small-scale clinical studies have found promising results showing that MxA levels enable the differentiation of viral and bacterial infections. [5][6][7][8][9] The present prospective multicenter study was undertaken to confirm these findings in routine practice conditions in a larger patient population including different clinical syndromes and infections with different bacterial and viral pathogens. …”
Section: What This Study Addsmentioning
confidence: 66%
“…5,6,9,19 The thresholds chosen differed from 1 study to another, ranging from 36.7 ng/mL to 500 ng/mL, 6,19,20 related to methodologic MxA detection differences, ROC curve analyses, or desired Se or Sp. In our study, MxA levels above the 200-ng/mL threshold predicted a viral infection with useful LRs for practice.…”
Section: Validation Of Mxa As a Marker Of Viral Infectionmentioning
confidence: 99%
“…It is expected that this type of response would impact the clinical presentation of the disease, and thus our study provides clues as to the effectors of H1N1pdm virulence. In fact, expression of Mx-A, the human counterpart of MX-1 in blood, has been used as marker to differentiate between viral and bacterial infection in febrile children (43,44). However, at this time, it is not clear how different respiratory viruses (including different human strains of influenza virus) regulate the expression of systemic IFN, since its augmentation in blood has been detected for some (e.g., coxsackievirus, adenovirus, respiratory syncytial virus, and cytomegalovirus) (45) but was not found for others (e.g., rhinovirus) (46).…”
Section: Discussionmentioning
confidence: 99%
“…Fever is the most frequent reason for presentation at the pediatric emergency department (PED) [1][2][3][4][5]. The percentage of patients who attend the PED due to fever ranges from 10.5 to 25% [3].…”
Section: Introductionmentioning
confidence: 99%
“…Fever is an important clinical sign because of the association of an underlying infection, although most infections are viral. However, a small group of these children may have a serious bacterial infection as the cause of the fever [2,3,[5][6][7]. One of the greatest challenges to physicians caring for febrile children in the PED is therefore the risk of an occult bacteremia (OB) [8,9].…”
Section: Introductionmentioning
confidence: 99%